THERMAL EFFECTIVENESS OF THE GAS FLOW VORTICAL HEATRELEASE INTENSIFICATION AT AXIAL AND TRANSVERSAL FLOWING-AROUND THE ROUND-TUBULAR SURFACES Part 2 - V. B. Kuntysh; A. B. Sukhotskiy; A. V. Yatsevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The paper demonstrates the fact that in valuating the actual heat efficiency from utilizing the vortical heat-release intensification it is necessary to account for the increase of heatreleasing area of the tube with the corresponding lacunae (hollows, lunules). It may vary from 4 to 280 % as a function of their geometrical parameters which causes heat-release increasing with its simultaneous growth from vortex formation in the boundary-layer flow by the swirls generated by lunule turbulizers. For the tube of axial flow-around with hollows applied on the outer surface the vortex intensification enhances the thermal effectiveness up to 1,39 times, and in the case of the transversal flow-around tube banks with lunuled tube outer surface it does not exceed 29 % at Re = 5000. With Re number growing to 14000 the energy effect tangibly declines to 6 %.The thermal effectiveness of the vortex intensification with spherical lunules on the tube inside surface and the air moving inside does not exceed 13 % in the interval Re = (1−2) ⋅ 104 , which is distinctive for air the preheaters of steam-boilers. However, a greater energy effect (up to 33 %) for the axial flowing is attained from emerging saliences on the tube inside surface beneath the spherical lacunae on the outside. The authors establish that employing discrete roughness in the form of transverse circular saliences (diaphragms) allows attaining much greater heat-emission intensification (up to 70 %) in the interval of Re = (10−100) ⋅ 103 as compared to the smooth tube. The paper shows that physical principles of the heat-emission vortex intensification by way of lunuling the round tubular surfaces differentiate from those applying artificial limited roughness in the form of pyramid frusta on the tube outside surfaces flowed around by the transverse flow.